pHlash: a new genetically encoded and ratiometric luminescence sensor of intracellular pH. - Yunfei Zhang; Qiguang Xie; J Brian Robertson; Carl Hirschie Johnson (PLoS ONE, 2012)
We report the development of a genetically encodable and ratiometic pH probe named "pHlash" that utilizes Bioluminescence Resonance Energy Transfer (BRET) rather than fluorescence excitation. The pHlash sensor-composed of a donor luciferase that is genetically fused to a Venus fluorophore-exhibits pH dependence of its spectral emission in vitro. When expressed in either yeast or mammalian cells, pHlash reports basal pH and cytosolic acidification in vivo. Its spectral ratio response is H(+) specific; neither Ca(++), Mg(++), Na(+), nor K(+) changes the spectral form of its luminescence emission. Moreover, it can be used to image pH in single cells. This is the first BRET-based sensor of H(+) ions, and it should allow the approximation of pH in cytosolic and organellar compartments in applications where current pH probes are inadequate.